Develop a Digital Module of PAI Learning Using Anyflip Web to Increase Learning Motivation - Andriani, Silvi; Triani, Dewi Agus; Syahidah, Nila Lukmatus (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
PAI learning is still general and has not improved other teaching materials so the learning motivation of students is low. This study aims to 1) develop teaching materials, namely the PAI and Budi Pekerti learning modules using the anyflip web for class III students at SD Negeri 1 Sekaran, and 2 increase students' learning motivation. This research and development use the R&D (Research and Development) method with the ADDIE research model. The results of research and development of PAI and Budi Pekerti learning modules use the anyflip web. The module gets a student response test of 97.9% from the small group test and 98.1%, which means that students are interested in interesting pictures and like to listen to audio. The percentage before using the module was 69.6% and the percentage after using the module by distributing questionnaires to find out an increase in students' learning motivation by 82.9% which showed students were more diligent in facing assignments and tenacious in facing difficulties. The result shows significant results in increasing learning motivation because, in the anyflip web, there are audio and also interesting images that are adapted to the age of students in grade 3 elementary school, where the age of grade 3 elementary school children is included in the operational thinking category, which means being able to think logically with the help of concrete objects. So to create students who can think logically, concrete objects are needed, one of which is the anyflip web in the learning process.